Из опыта создания первого болгарско-польского и польско-болгарского фразеологического словаря: проблемы и решения - Blagoeva, Diana; Sosnowski, Wojciech (Wiener Slawistischer Almanach, 2023)
The article presents the methodology employed in creating The dictionary of active Bulgarian and Polish phraseology [Речник на активната фразеология в българския и полския език / Leksykon aktywnej frazeologii bułgarskiej i polskiej], the first Bulgarian-Polish/Polish-Bulgarian phraseological dictionary in Slavic lexicography. The authors discuss problems associated with the development and refinement of the concept underlying the dictionary and its compilation. They then present their solutions relating to the problems of defining the concept of phraseological units in the Bulgarian and Polish linguistic traditions, the principles used in the selection and verification of phraseological material, and ways of presenting lexicographic information in the dictionary. The article includes various examples of active phraseological units from both languages.